On registration of spontaneous electromagnetic emission of lithosphere within lengthy salt adit - Zakharov, I. G.; Shuman, V.N. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2014)
Results of measurements of impulse current of electromagnetic emission within frequency range 2,5-50kHz (by 3 dB level) in rectilinear horizontal part of natural salt 700 m long adit situated at the depth of 260m and without any technical sources of noise have been presented. Registration of impulse current of emission at the site of observation located at the surface above the adit was being conducted synchronously and by the instrument of the same type. In addition non-synchronous measurements of impulse current along the profile situated on the surface under acute angle to the course of the adit have been carried out. The component of spontaneous electromagnetic emission of lithosphere origin has been distinguished in the frequency range under consideration without noise bar from the sources of atmosphere-ionosphere-magnetosphere origin. Comparative analysis of impulse current records obtained at the day surface and in the adit with the depth exceeding the thickness of the skin-layer within the frequency ranges 2,5-50 kHz has been given and their geological-geophysical interpretation has been proposed.